Найти корень уравнения
0,6 - 1,6(х-4) = 3(7-0,4х)

Lucky0ne Lucky0ne    1   16.04.2020 17:29    0

Ответы
никита42728 никита42728  13.10.2020 09:32

0,6 - 1,6(х-4) = 3(7-0,4х)

0,6-1,6*х -1,6*(-4)=3*7+3*(-0,4х)

0,6 - 1,6х + 6,4 = 21 - 1,2х

7 - 1,6х = 21 - 1,2х

1,2х - 1,6х = 21 - 7

-0,4х = 14

х = 14 : (-0,4)

х = -35

ПОКАЗАТЬ ОТВЕТЫ
глупыйенот глупыйенот  13.10.2020 09:32

-35

Пошаговое объяснение:

0,6-1,6(х-4)=3(7-0,4х)

0,6-1,6х+6,4=21-1,2х

-1,6х+1,2х=21-0,6-6,4

-0,4х=14   /÷(-0,4)

  х= -35

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика